PENERAPAN MODEL MALCOLM BALDRIDGE DALAM PENGUKURAN KINERJA ORGANISASI PENDIDIKAN - Ahmad, Frischa Alviannisya; Sohiron, Sohiron (Jurnal Manajemen Pendidikan, 2026)
This research aims to comprehensively describe the application of the Malcolm Baldrige model in measuring the performance of educational organizations in Indonesia. In the era of globalization and educational transformation, educational institutions are required to implement measurable, directed, and sustainable quality management systems. The Malcolm Baldrige Excellence Framework (MBEF) provides systematic guidance through seven key categories: leadership, strategic planning, customer focus, measurement and data analysis, workforce management, operational processes, and results. This study applies a qualitative approach using a literature review method from various national academic sources, including textbooks and journals discussing the implementation of the Baldrige model in Indonesian education. The analysis reveals that the Baldrige model is effective in improving institutional performance, particularly in data-driven decision-making, strategic planning, and stakeholder satisfaction. The main challenges include limited human resources, lack of managerial training, and weak quality culture in some educational institutions. Therefore, it is crucial for educational institutions to integrate the Baldrige model into their internal quality assurance systems (SPMI) to achieve continuous and competitive quality improvement.